A direct comparison of the diagnostic efficacy of alternative scaffoldbased radiopharmaceuticals [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE)3-G3 in patients with HER2-positive breast cancer - O. D. Bragina; S. M. Deyev; E. Yu. Garbukov; V. E. Goldberg; V. I. Chernov; V. M. Tolmachev (Бюллетень сибирской медицины)
Aim. To perform a direct comparison of the diagnostic efficacy of [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE) -G3 in HER2-positive breast cancer patients before the systemic treatment.Materials and methods. The study included 11 patients with HER2-positive breast cancer (T1–4N0–2M0–1) before the initiation of systemic treatment. All patients underwent a radionuclide examination with [99mTc]TcADAPT6 and [99mTc]Tc-(HE) -G3 with the interval of 3–4 days. Single-photon emission computed tomography (SPECT) /computed tomography (CT) was performed 2 and 4 hours after [99mTc]Tc-ADAPT6 and [99mTc]Tc(HE)3-G3 administration, respectively.Results. The analysis of [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE) -G3 distribution showed their high uptake in the kidneys and liver. Breast tumors were visualized in all cases. The average tumor uptake of [99mTc]Tc-ADAPT6 was 4.7 ± 2.1, which was significantly higher than in the [99mTc]Tc-(HE)3-G3 injection (3.5 ± 1.7) (p < 0.005, paired t-test). The tumor-to-background ratio (15.2 ± 7.4 and 19.6 ± 12.4, respectively) had no statistical differences in both cases (p > 0.05, paired t-test). Liver metastases were visualized in patients 1 and 5 and corresponded to the projection of metastases according to contrast-enhanced abdominal CT. The accumulation of [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE)3-G3 in the projection of metastases in both cases was significantly higher compared to the primary tumor (1.3 and 1.7 times higher in patient 1; 2.2 and 3.5 times higher in patient 5, respectively).Conclusion. Both [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE)3-G3 demonstrated the diagnostic efficacy in visualizing a primary HER2-positive tumor in breast cancer patients. However, [99mTc]Tc-ADEPT6 had higher accumulation values, which makes it a more promising diagnostic agent.